Serine-47 phosphorylation of cytochrome c in the mammalian brain regulates cytochrome c oxidase and caspase-3 activity - Kalpage, Hasini A. (FASEB J, 2019)
Cytochrome c (Cytc) is a multifunctional protein that operates as an electron carrier in the mitochondrial electron transport chain and plays a key role in apoptosis. We have previously shown that tissue-specific phosphorylations of Cytc in the heart, liver, and kidney play an important role in the regulation of cellular respiration and cell death. Here, we report that Cytc purified from mammalian brain is phosphorylated on S47 and that this phosphorylation is lost during ischemia. We have characterized the functional effects in vitro using phosphorylated Cytc purified from pig brain tissue and a recombinant phosphomimetic mutant (S47E). We crystallized S47E phosphomimetic Cytc at 1.55 Å and suggest that it spatially matches S47-phosphorylated Cytc, making it a good model system. Both S47-phosphorylated and phosphomimetic Cytc showed a lower oxygen consumption rate in reaction with isolated Cytc oxidase, which we propose maintains intermediate mitochondrial membrane potentials under physiologic conditions, thus minimizing production of reactive oxygen species. S47-phosphorylated and phosphomimetic Cytc showed lower caspase-3 activity. Furthermore, phosphomimetic Cytc had decreased cardiolipin peroxidase activity and is more stable in the presence of H(2)O(2). Our data suggest that S47 phosphorylation of Cytc is tissue protective and promotes cell survival in the brain.—Kalpage, H. A., Vaishnav, A., Liu, J., Varughese, A., Wan, J., Turner, A. A., Ji, Q., Zurek, M. P., Kapralov, A. A., Kagan, V. E., Brunzelle, J. S., Recanati, M.-A., Grossman, L. I., Sanderson, T. H., Lee, I., Salomon, A. R., Edwards, B. F. P, Hüttemann, M. Serine-47 phosphorylation of cytochrome c in the mammalian brain regulates cytochrome c oxidase and caspase-3 activity.